Perilaku Manusia Dalam Filsafat Ekonomi Islam - Hermansyah Hermansyah (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2015)
Humans are basically predisposed negative predisposition, Recognizing the negative elements in the form of lust soul (al-hawa, al-syahwah), then the best way to fight lust other than through education (ta'dib), is through training (al-tajribah, al-mu'anah, and al-riyadhah). Therefore, author wanted to explain the need for guidance to align human behavior is based on the concept of economic philosophy of Islam and Islam as a benchmark will give birth to the Islamic mindset and if practiced will lead to a pattern of behavior that is worth Worship Islamic. In general it can be called: basically Human behavior can be directed and patterned suit establishmen their shapes, an important role or even very important in the context of this establishment, good education comes from ling-kungan family, school, and the environmental community, and the policy and the will of the government.